Prevalence and Antimicrobial Susceptibility Pattern of Bacterial Isolates in a Tertiary Care Hospital: A Retrospective Study - Divyashanthi, C. M.; Adithiyakumar, S.; Bharathi, N. (Technological Innovation in Pharmaceutical Research Vol. 7, 2021)
Background: Antimicrobial drugs includes all agents that work against a variety of microorganisms such as bacteria, viruses, fungi and parasites. Antimicrobial resistance is when bacteria or other microbes become resistant to the effects of a drug after being exposed to them. Bacterial species insusceptible to a particular drug are naturally resistant. Species that were once sensitive but eventually become resistant to it are said to have acquired resistance. Objective: Many human illnesses are bacterial in origin which can be treated with appropriate antibiotics and selection of these is mostly based on culture and sensitivity. The problem of antimicrobial resistance has burgeoned throughout the world both in inpatients and outpatients. We must work together to preserve the power of antimicrobials so as to use these effectively in treating diseases. The aim of the study is to find out the prevalence of infection and sensitivity pattern among bacterial pathogens in a tertiary care hospital. Methods: This retrospective study was carried out in Vinayaka Missions Medical College and Hospital, Karaikal, Puducherry (U. T) to study the culture and sensitivity pattern of clinical isolates from blood, urine, sputum, wound, ear/throat swab for one year (June 2012- June 2013). The positive cultures and their antibiotic susceptibility testing were performed under the guidelines of Clinical and Laboratory Standard Institute (CLSI). The lab data from Microbiology department were utilized and filled in a proforma and analyzed. Results: Out of 788 samples, 296 were culture positive. Isolated bacteria were mostly Gram negative organisms (GNO) of which Klebsiella (41.55%) was commonly followed by Pseudomonas (15.20%), Escherichia coli(4.05%) and Proteus (3.71%). Among Gram positive organisms (GPO) Staphylococcus (35.47%) was common. Imipenem (100%), Gentamycin (90.20%), Amikacin (89.14%), were the antimicrobials most sensitive for GNO, while Ceftriaxone (100%), Cefotaxime (100%), Nitrofurantoin(96.15%) and Linezolid(92.13%) were most sensitive for GPO. Widespread resistance to Nalidixic acid (99%), Ampicillin (85.90%), Cefuroxime (75%) is seen in both groups, while Cefazolin(79.25%) and Norfloxacin(83%) was noted for GNO, resistance to Amoxicillin with clavulanic acid (81.66%) and Imipenem(55.55%) was noted for GPO. Conclusion: The technical abilities to detect novel, resistant mechanisms and to overcome the microbial resistance has to be improved. Antibiotic policies agreed among clinicians, microbiologists and pharmacologists will guide good prescribing, provide maximum coverage for treating infections and ensure antibiotic cycling.